Verlust der Mitte oder Neuzentrierung?: neuere Wege in der Christologie - Buntfuß, Markus (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2004)
Assuming the central importance of Christology in Protestant theology, the author reconstructs its recent history as a process of dogmatic alienation from Christ the incarnation of God and of historical alienation from the earthly Jesus. Following this, three present-day christological models are characterised which attempt a christological re-centering of the Christian religion. They are distinguished according to their respective methodical orientation towards the paradigms of consciousness, of culture and of language. The question to what extent they are able to relate the scientific perspective of the observer with the religious perspective of the participant and to make them productive for one another, serves as a criterion of their plausibility.